Mast cells in colorectal cancer tumour progression, angiogenesis, and lymphangiogenesis - Liu, Xiaoxin; Li, Xinyu; Wei, Haotian; Liu, Yanyan; Li, Ningxu (Frontiers in Immunology, 2023)
The characteristics of the tumor cells, as well as how tumor cells interact with their surroundings, affect the prognosis of cancer patients. The resident cells in the tumor microenvironment are mast cells (MCs), which are known for their functions in allergic responses, but their functions in the cancer milieu has been hotly contested. Several studies have revealed a link between MCs and the development of tumors. Mast cell proliferation in colorectal cancer (CRC) is correlated with angiogenesis, the number of lymph nodes to which the malignancy has spread, and patient prognosis. By releasing angiogenic factors (VEGF-A, CXCL 8, MMP-9, etc.) and lymphangiogenic factors (VEGF-C and VEGF-D, etc.) stored in the granules, mast cells play a significant role in the development of CRC. On the other hand, MCs can actively encourage tumor development via pathways including the c-kit/SCF-dependent signaling cascade and histamine production. The impact of MC-derived mediators on tumor growth, the prognostic importance of MCs in patients with various stages of colorectal cancer, and crosstalk between MCs and CRC cells in the tumor microenvironment are discussed in this article. We acknowledge the need for a deeper comprehension of the function of MCs in CRC and the possibility that targeting MCs might be a useful therapeutic approach in the future.